Martin Lopez-Zubero's Left-arm Pull at 180 m of His 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992 - Rushall, B. S. (1999)
Video pictures (9 frames) and the appropriate technical/ biomechanical explanations for Martin Lopez-Zubero's Left-arm Pull at 180 m of His 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992. In this sequence, the right leg kicks three times while the left leg only kicks once (frames #3-4).